2019
DOI: 10.3390/genealogy3040071
|View full text |Cite
|
Sign up to set email alerts
|

“I Always Wanted to Look at Another Human and Say I Can See That Human in Me”: Understanding Genealogical Bewilderment in the Context of Racialised Intercountry Adoptees

Abstract: Although there is growing literature on the situation of international adoption, there is a general paucity of research into the salience of the concept of genealogical bewilderment (GB) and racialised adult adoptees’ experiences of searching for their transnational birth families. This paper seeks to explore the relevance of the much under-studied concept of GB in relation to intercountry adoption. Through a detailed analysis of a documentary film series—Searching for Mum—that serves as an empirical example t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…. there’s all the kids and there’s me, standing way up here above everyone.” While integrating within the adoptive family is important developmentally and an adaptive mechanism, the disconnection between internal experience and external appearance can be angst-inducing, disconcerting, and generate identity diffusion (Barn & Mansuri, 2019), additional challenges which adoptees need to traverse.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…. there’s all the kids and there’s me, standing way up here above everyone.” While integrating within the adoptive family is important developmentally and an adaptive mechanism, the disconnection between internal experience and external appearance can be angst-inducing, disconcerting, and generate identity diffusion (Barn & Mansuri, 2019), additional challenges which adoptees need to traverse.…”
Section: Resultsmentioning
confidence: 99%
“…Various research attempts to document how adoption is a complex interplay of biological, social, psychological and cultural elements and a myriad of conditions exist to describe the problems adoptees present with, problems that often have psychological underpinnings. These include genealogical bewilderment (Barn & Mansuri, 2019; Sants, 1964), adopted child syndrome (Kirschner & Nagel, 1988; J. Smith, 2001), cumulative adoption trauma (Lifton, 2002) and psychic homelessness (Hoksbergen, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Haimes (2006) noted, knowing one’s genetic origin is an innate need for a stable sense of identity. Without such knowledge, an individual may suffer from genealogical bewilderment and identity confusion (Kernreiter et al, 2020), which can lead to psychological distress and mental health difficulties (Barn & Mansuri, 2019). Indeed, a study by Tieman et al (2008) showed that adult adoptees who searched for their genetic roots presented more psychiatric problems.…”
Section: Resultsmentioning
confidence: 99%
“…Genealogical bewilderment is still recognised today as a difficulty associated with adoption (Barn & Mansuri, 2019).…”
Section: The Adoption Experience and Potential Implicationsmentioning
confidence: 99%